2000
DOI: 10.1080/00071660050022263
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chickens to microbial phytase supplementation as influenced by dietary phytic acid and non-phytate phosphorous levels. II. Effects on apparent metabolisable energy, nutrient digestibility and nutrient retention

Abstract: 1. Male broilers (n=900) were fed on wheat-sorghum-soyabean meal based diets containing 3 concentrations of phytic acid (10.4, 13.2 and 15.7 g/kg; equivalent to 2.9, 3.7 and 4.4 g/kg phytate P), 2 concentrations of non-phytate (or available) phosphorus (2.3 and 4.5 g/kg) and 3 concentrations of microbial phytase (0, 400 and 800 FTU/kg) from day 7 to 25 post-hatch. The dietary concentrations of phytic acid were manipulated by the inclusion of rice pollards. All diets contained celite (20 g/kg) as a source of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
123
4
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 17 publications
20
123
4
7
Order By: Relevance
“…Os resultados de desempenho obtidos neste ensaio (1 a 7 dias) sugerem que a fitase (500 ftu/kg de ração) foi eficiente em liberar parte do fósforo fítico presente nas rações. Isso concorda com vários autores que relataram a ação benéfica dessa enzima sobre os grupamentos fíticos (Ravindran et al, 2000;Kornegay, 2001;Choct, 2006 Tabela 3 -Desempenho de frangos de corte, no período de 1 a 7 dias de idade, alimentados com rações contendo fitase e diferentes níveis de fósforo disponível e cálcio resultados de desempenho, pois é preciso considerar também a adequada mineralização óssea. Se comparadas à ração controle sem fitase, as rações avaliadas não acarretaram diferença significativa (P>0,05) na porcentagem de cinzas ósseas (Tabela 4).…”
Section: Resultsunclassified
“…Os resultados de desempenho obtidos neste ensaio (1 a 7 dias) sugerem que a fitase (500 ftu/kg de ração) foi eficiente em liberar parte do fósforo fítico presente nas rações. Isso concorda com vários autores que relataram a ação benéfica dessa enzima sobre os grupamentos fíticos (Ravindran et al, 2000;Kornegay, 2001;Choct, 2006 Tabela 3 -Desempenho de frangos de corte, no período de 1 a 7 dias de idade, alimentados com rações contendo fitase e diferentes níveis de fósforo disponível e cálcio resultados de desempenho, pois é preciso considerar também a adequada mineralização óssea. Se comparadas à ração controle sem fitase, as rações avaliadas não acarretaram diferença significativa (P>0,05) na porcentagem de cinzas ósseas (Tabela 4).…”
Section: Resultsunclassified
“…Furthermore, several studies showed that added phytase improved ileal amino acid digestibility in individual feed ingredients (Ravindran et al, 1999;Rutherfurd et al, 2002) and in complete diets (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 2000). However, this topic remains still controversial because in some other experiments only marginal or even no effects were observed (Sebastian et al, 1997;Biehl and Baker, 1997;Zhang et al, 1999;Peter et al, 2000).…”
mentioning
confidence: 99%
“…In recent years, some researchers reported that microbial phytase had a beneficial effect on the utilization of nutrients other than phosphorus, such as amino acids (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 1999Ravindran et al, , 2000. Furthermore, several studies showed that added phytase improved ileal amino acid digestibility in individual feed ingredients (Ravindran et al, 1999;Rutherfurd et al, 2002) and in complete diets (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 2000).…”
mentioning
confidence: 99%
“…Inclusion of enzymes in plant diets enables the birds to degrade the antinutritive feed components along with promoting the breakdown of starch, cell walls, and storage proteins (10). However, many previous researchers have reported that the efficacy of such enzymes seems to be unpredictable in some cases and depends partially on the substrate or the nature of the diet composition including many other factors (11)(12)(13). The current study was undertaken to assess the relative nutritional merits of the two leading vegetable protein sources, SBM and CM, when fed with or without carbohydrase (Avizyme) and phytase enzyme supplements.…”
Section: Introductionmentioning
confidence: 99%